Expert system for the identification and control of weeds in wheat crop - Islam, Shahnawazul; Sharma, R.K.; Chhokar, R.S.; Dhar, Shiva; Sabir, Naved; Chaturvedi, K.K.; Singh, Randhir; Farooqi, Mohd. Samir; Sharma, Kirti (Annals of Agricultural Research, 2017)
Effective weed management is important for a successful wheat production. Inadequate weed controlcan lead to significant yield loss and harvest problems. One of the pre-requisite of efficient weedmanagement is proper weed identification so that suitable strategies are selected. An Expert Systemon Wheat Crop Management has been developed by ICAR-IASRI, New Delhi with the collaborationof ICAR-IARI, New Delhi, ICAR-IIDWR. Karnal and ICAR-NCIPM, New Delhi. This system has acrop protection module that carries a sub module on weed management. The module helps inidentifying weeds and suggests treatment to minimize the production loss. The system carriesinformation of about 23 major weeds affecting wheat crop and its management stored in itsknowledge base. The system works as an information bank for wheat growing farmers that canhelp them in better crop management in order to enhance productivity and production of wheat inthe country. The system is available at the URL http://www.iasri.res.in/wheat